2000
DOI: 10.1002/1098-2361(2000)19:5<369::aid-zoo7>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography of the estrous cycle in female African elephants (Loxodonta africana)

Abstract: The endocrinology of the elephant estrous cycle has been well characterized, but little emphasis has been placed on evaluating corresponding changes in the reproductive tract. Ultrasound was used to document changes in reproductive tract morphology throughout the estrous cycle in four cycling female African elephants. During a 7‐month period, frequent ultrasound examinations (n = 190) during the luteal and non‐luteal phase were compared with serum progesterone and luteinizing hormone (LH) concentrations during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
0
2

Year Published

2000
2000
2010
2010

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 20 publications
3
52
0
2
Order By: Relevance
“…During the follicular phase in African elephants, the occurrence of two follicular waves, each terminated by an LH peak, has been previously reported (Hermes et al 2000). The authors hypothesized that the first LH peak induced luteinization of subordinate follicles from the first wave.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…During the follicular phase in African elephants, the occurrence of two follicular waves, each terminated by an LH peak, has been previously reported (Hermes et al 2000). The authors hypothesized that the first LH peak induced luteinization of subordinate follicles from the first wave.…”
Section: Discussionmentioning
confidence: 99%
“…Our measurements of CLs in cycling Asian elephants did not exceed 4.1 cm. Similarly, in nonpregnant African elephants, Hanks & Short (1972) reported cyclical CL sizes of 2.4-3.3 cm in culled animals while Hermes et al (2000) reported an average diameter of 2.58G0.45 cm (range: 2.3-3.8 cm) for CLs observed by ultrasound. This suggests that CLs are significantly larger during gestation than during the cycle.…”
Section: Luteogenesis In Elephantsmentioning
confidence: 95%
See 3 more Smart Citations